2018
DOI: 10.3389/fmars.2018.00228
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Aquaculture Chemotherapeutants in Flocculent Matter Collected at a Hard-Bottom Dominated Finfish Site on the South Coast of Newfoundland (Canada) After 2 Years of Fallow

Abstract: The expansion of aquaculture is resulting in sites being installed over a diversity of substrate types, leading to different potential chemotherapeutant degradation scenarios. There is little to no information on the biodegradation and/or persistence of chemotherapeutants at hard-bottom dominated aquaculture sites having little natural sediment. In this study, we measured organic matter (OM) content and concentrations of chemicals linked to finfish aquaculture activities (trace elements, antibiotics and parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Similarly, for aquaculture sites in southwestern New Brunswick, Canada, and the San Pedro River, Spain, Cu, Cd, Zn, and Pb were also considered aquaculture markers and were signi cantly linked to OM in the sediments (Mendiguchía et al, 2006;Chou et al, 2002). Cu, Zn, and P were aligned with organic enrichment indicators in the Maritimes and British Columbia aquaculture environments of Canada (Sutherland et al, 2007;Sutherland, 2011), and Zn and Cd tended to correlate with OM in the sediments of the South Coast of NL, Canada (Hamoutene et al, 2018). In sediment from a core adjacent to a marine n sh farm in Lime Kiln Bay, Canada, the increase in Cd was also found to be a result of not only authigenic enrichment but also the high ux of organic materials discharged from sh farm wastes (Smith et al, 2005).…”
Section: Metal Concentrations In Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, for aquaculture sites in southwestern New Brunswick, Canada, and the San Pedro River, Spain, Cu, Cd, Zn, and Pb were also considered aquaculture markers and were signi cantly linked to OM in the sediments (Mendiguchía et al, 2006;Chou et al, 2002). Cu, Zn, and P were aligned with organic enrichment indicators in the Maritimes and British Columbia aquaculture environments of Canada (Sutherland et al, 2007;Sutherland, 2011), and Zn and Cd tended to correlate with OM in the sediments of the South Coast of NL, Canada (Hamoutene et al, 2018). In sediment from a core adjacent to a marine n sh farm in Lime Kiln Bay, Canada, the increase in Cd was also found to be a result of not only authigenic enrichment but also the high ux of organic materials discharged from sh farm wastes (Smith et al, 2005).…”
Section: Metal Concentrations In Sedimentsmentioning
confidence: 99%
“…For British Columbia, Maritimes, and Newfoundland and Labrador region, Canada, 95 (17.8%), 104 (19.5%), 23 (4.3%), and 25 (4.7%) of all sampled stations (n = 533) from sh cage (0-500 m) were enriched with respect to Cu (31.5-241 mg kg-dry − 1 ) and Zn (93.7-670 mg kg-dry − 1 )(Hamoutene et al, 2021). Exceeding levels of Cu and Zn were also presented around sh cages and were assumed to be the direct causes of aquaculture wastes of occulent matter in the South Coast of Newfoundland (27.4-66.0 mg kg-dry − 1 for Cu and 58-726 mg kg-dry − 1 for Zn) and several salmon farms of southwestern New Brunswick (9.1-26.7 mg kg-dry − 1 for Cu and 48.8-102.6 mg kg-dry − 1 for Zn), Canada(Hamoutene et al, 2018;Yeats et al, 2005); Stations enriched in Zn and Cu have been found close to 200 mg kg − 1 (> 250 mg kg − 1 for Zn and > 70 mg kg − 1 for Cu) in Lime Kiln Bay, New Brunswick, Canada(Smith et al, 2005). For the farms on Stewart Island and New Zealand, high levels of Cu ranging from 48 to 150 mg kg − 1 for Cu and 410 mg kg − 1 of Zn were also reported at sampling sites near marine farms(Brooks & Mahnken, 2003).…”
mentioning
confidence: 99%
“…Copper originating from salmon feed or the antifoulants of the net cages may accumulate in soft sediments and in flocculent matter settled on hard bottom underneath and near fish farms (Hamoutene et al 2018, Grefsrud et al 2021) and consequently impact marine fauna. Copper is essential for all organisms in very small levels (therefore added to the feed) but becomes toxic at higher concentrations.…”
Section: Coral Metabolismmentioning
confidence: 99%